PROFILE OF PARTNERSHIP SYSTEM OF BROILER LIVESTOCK FARMING WITH CLOSE HOUSE SYSTEM IN MALANG REGENCY - Pradiptya Ayu Harsita; amam amam (UPT Penerbitan Universitas Jember, 2017)
Partnership system is business collaboration between mikro business with intermediate business and/or makro business that followed with founding from mikro business and/or makro business with showed principle of need each other, mutual need, and mutual benefit. The aim of this research was to (1) formulated profile business partnership system of broiler livestock farming with close house system in malang regency and (2) committed analysis of Production Cost of broiler livestock farming with partnership system. Analysis of the data was used descriptive analysis. The result showed that (a) There are three models of partnership system of broiler livestock business with close house system in malang regency namely profit sharing system, sub-contract system, and management fee system; and (b) Analysis of the costs production in all of partnership system that observed during one year or period six. The result of analysis of Production Cost with profit sharing system during one period of Rp. 16.180/kg, during two period of Rp. 15.294/kg, during three period of Rp. 14.064/kg, during four period of Rp. 8.090/kg, during five period of Rp. 14.840/kg,during six period of Rp. 15.510/kg. The result of analysis of Production Cost with sub-contract system during one period of Rp. 15.281/kg, during two period of Rp. 15.263/kg, during three period of Rp. 17.331/kg, during four period of Rp. 18.455/kg, during five period of Rp. 14.159/kg, during six period of Rp. 13.621/kg. The result of analysis of Production Cost with management fee system during one period of Rp. 14.558/kg, during two period of Rp. 17.311/kg, during three period of Rp. 17.927/kg, during four period of Rp. 15.924/kg, during five period of Rp. 15.214/kg, during six period of Rp. 16.905/kg.